2009
DOI: 10.3758/pbr.16.6.1100
|View full text |Cite
|
Sign up to set email alerts
|

Action goals influence action-specific perception

Abstract: We examined the processes that mediate the emergence of action-specific influences on perception that have recently been reported for baseball batting and golf putting (Witt, Linkenauger, Bakdash, & Proffitt, 2008;. To this end, we used a Schokokusswurfmaschine: Children threw a ball at a target, which, if hit successfully, launched a ball that the children then had to catch. In two experiments, children performed either a throwing-and-catching task or a throwing-only task, in which no ball was launched. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…Apparently, this modulation of perception does not depend on the intention to overcome the judged distance. This indicates that the effect of transportation devices on perception cannot be entirely due to moment-to-moment perception of one's own potential (see e.g., Cañal-Bruland & van der Kamp, 2009;Lee et al, 2012;. Instead, the mere availability of a car modulated perception as compared to participants without a car (evidenced by the comparison of the initial distance estimations of pedestrians and drivers).…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, this modulation of perception does not depend on the intention to overcome the judged distance. This indicates that the effect of transportation devices on perception cannot be entirely due to moment-to-moment perception of one's own potential (see e.g., Cañal-Bruland & van der Kamp, 2009;Lee et al, 2012;. Instead, the mere availability of a car modulated perception as compared to participants without a car (evidenced by the comparison of the initial distance estimations of pedestrians and drivers).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the secondary criteria was to differentiate articles where the goal of the task was not to get to the end of the route (but, for example the task consisted of participants adopting an instructed posture). The logic behind this exclusion criteria was that previous studies have demonstrated that task goals have important impacts on skilled coordination [64,65]. Studies were recorded in separate tables.…”
Section: Trodu Tiomentioning
confidence: 99%
“…Although people may not remember the location of the nearest fire extinguisher, they can locate a bright red object when this becomes goal relevant (hopefully, in the case of a real fire). It may be that when goals become activated, people can execute action-specific programs (e.g., Cañal-Bruland & van der Kamp, 2009) that enable them to locate a previously unnoticed fire extinguisher. However, in the event of a fire, environmental and internal conditions (e.g., smoke in a hallway, anxiety, and stress), could potentially compromise perceptual and goal-relevant cognitive operations (cf., Vendetti, Knowlton, & Holyoak, 2012), such that the person would need to rely on memory to find a fire extinguisher.…”
Section: Objects (Per Floor)mentioning
confidence: 99%